The Practice of Religious Plurality in The Indonesian National Army - Didik Suwarno; Siti Ma'sumah; Abdul Basit (LAFADZ JAYA Publisher, 2023)
This paper discusses the practice of religious plurality within the Indonesian Armed Forces. To support the main task of soldiers and the success of the task, they are equipped with faith and purity, good moral values and noble character. Religion has a significant role in supporting military tasks. Data collection techniques in this study used observation then, followed by interviews. Forms behaviour The TNI AD in maintaining harmony between members of different religions includes anjangsana, working together to achieve common goals in religion, sympathy and empathy, tolerance and mutual respect. Adaptation conducted interfaith religious packed reasonably. Goal TNI AD attachment is the goal achieved that is harmony and tolerance Inter-religion. Function Integration TNI AD is carried out by issuing governing policies about members of TNI AD, which religious Islam, Christian, Hindu and Buddhist for holding religious ceremonies simultaneously on the day and at the time same. That is day Friday o'clock 18.30 WIB. The system of Latent Maintenance, which the Indonesian Army maintains, improves individual motivation and the cultural patterns that create and maintain the motivation.